Formación de Recuerdos Flashbulb en población colombiana (2023)
The present research examines the formation of flashbulb memories in a sample of Colombians. Flashbulb Memories (FBM) are autobiographical memories related to the context of receiving shocking public news. A sample of 380 respondents (171 men and 209 women) aged from 20 to 89 years old (M = 37.05; SD = 13.36) conducted a test between 4-19 days after worldwide breaking news. Factor analysis, descriptive analysis and structural equation models were applied. Four models described by the literature on flashbulb memories were tested. Results show that models proposed by Finkenauer et al. (1998) and Er (2003) predict the formation of flashbulb memories through an indirect path. The models proposed by Brown and Kulik (1977) and Conway et al. (1994) do not predict the formation of flashbulb memories in news related to international terrorism. However, goodness of fit indexes were better for Brown and Kulik's model than for the other three models. © 2019 Pontificia Universidad Catolica del Peru. All Rights Reserved.